2003
DOI: 10.1016/s0006-3495(03)70065-4
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of ADP Diffusion and Regulation of Respiration in Cardiac Cells

Abstract: Heterogeneity of ADP diffusion and regulation of respiration were studied in permeabilized cardiomyocytes and cardiac fibers in situ and in silico. Regular arrangement of mitochondria in cells was altered by short-time treatment with trypsin and visualized by confocal microscopy. Manipulation of matrix volumes by changing K(+) and sucrose concentrations did not affect the affinity for ADP either in isolated heart mitochondria or in skinned fibers. Pyruvate kinase (PK)-phosphoenolpyruvate (PEP) were used to tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
98
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 83 publications
6
98
0
Order By: Relevance
“…Similarly, in ischemic hearts, various alterations in mitochondrial function such as the significant decrease in maximal respiration rate and half-saturation constant for ADP were observed in parallel with the changes in structural organization of the cardiac muscle cells (7,16). These experimental results suggest that there is a direct link between regulation of muscle cell energetics and structural organization of the cell (28).…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Similarly, in ischemic hearts, various alterations in mitochondrial function such as the significant decrease in maximal respiration rate and half-saturation constant for ADP were observed in parallel with the changes in structural organization of the cardiac muscle cells (7,16). These experimental results suggest that there is a direct link between regulation of muscle cell energetics and structural organization of the cell (28).…”
mentioning
confidence: 63%
“…In addition, kinetic studies have shown a direct supply of endogenous ADP from ATPases to mitochondria (30,34). Such interaction can be explained by the existence of localized intracellular diffusion restrictions (28,39). A mild treatment of the fibers with trypsin leads to the removal of these diffusion restrictions, and at the same time, distribution of mitochondria in the fiber is changed from regular arrangement in the control to random distribution after the treatment (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These are likely to include systems with relatively high rates of ATP production/consumption and distant sites of ATP utilization, such as in some muscle fibers with a higher aerobic capacity than examined here (Meyer et al, 1984;Stokes and Josephson, 1992;Vendelin et al, 2000;Saks et al, 2003;Suarez, 2003) or in the flagellum of spermatozoa, which has been the subject of many reaction-diffusion analyses (e.g. Nevo and Rikmenspoel, 1969;Tombes and Shapiro, 1985;Van Dorsten et al, 1997;Ellington and Kinsey, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Stephen T. Kinsey (Mainwood and Rakusan, 1982;Meyer et al, 1984;Hubley et al, 1997;Aliev and Saks, 1997;Kemp et al, 1998;Vendelin et al, 2000;Saks et al, 2003). The intracellular diffusive flux of high-energy phosphates is largely mediated by phosphagen kinases, such as creatine kinase (CK) and arginine kinase (AK), although the mechanistic details are still the subject of study (reviewed by Walliman et al, 1992;Ellington, 2001).…”
Section: Introductionmentioning
confidence: 99%